Global economic uncertainties and Southeast Asian economies - Suthiphand Chirathivat 1953-; Chongvilaivan, Aekapol ca. 20./21. Jh; Sabhasri, Chayodom ca. 20./21. Jh (Institute of Southeast Asian Studies, 2015)
The aftermath of the global economic breakdown in 2008–9 underscores the risks facing Southeast Asia's growth prospects. Although the region has demonstrated exceptional resilience to external shocks emanating from economic powerhouses around the globe, Southeast Asia is in dire need of an optimal policy mix of macroeconomic and trade policy measures that differ by country, underpin domestic demand, and revive domestic economies. This book offers in-depth, region-specific economic policy discourse that illuminates how a policy push is at work in the region, and sheds light on room for strengthening regional cooperation. This book aims to: (1) discuss the developments of macroeconomic and trade-policy mix against the backdrop of the eurozone sovereign debt crisis and economic prospects for major countries in Southeast Asia (i.e., Singapore, Thailand, Malaysia, Indonesia, and Vietnam); (2) assess the effectiveness of policy responses to the global economic unrest; (3) identify opportunities and challenges facing Southeast Asia in the midst of the global economic slump when developing Southeast Asia leverages on an ever-expanding role in the global business environment; (4) rethink the East Asian model of growth where enormous gains were driven principally by export demands from advanced economies; and (5) pioneer the key areas of regional cooperation and macroeconomic and trade policy reforms that may potentially strengthen regional economies